PERILAKU WARGA SEKOLAH DALAM IMPLEMENTASI ADIWIYATA DI SMK NEGERI 2 SEMARANG - Hidayati, Nanik (Rizki Offset, 2014)
Adiwiyata is a government program to succeed a sustainable educational development. It aims atÂ creating responsible school memberships in protecting and conserving environment through goodÂ school management. This is implemented by state vocational school 2 Semarang having wonÂ Adiwiyata Mandiri in 2013.This research is to explore State Vocational School 2 SemarangÂ membersâ âattitude on the implementation of adiwiyata program. The research employs descriptiveÂ qualitative approach. The data taken on this research are primary and secondary ones. TheÂ primary data refers to direct sources like the principal, teachers, administrative staffs, studentsÂ and school committee. The secondary data are taken from collecting written sources andÂ documents. The techniques of collecting data are through participation, interview, andÂ documentation. The data analysis involves reduction, presentation, and data verification.TheÂ result shows that four adiwiyata indicators comprising environmental based school policy,Â environmental school based curriculum, participative school based activity and environmentalÂ school based infrastructure have been successfully implemented at State Vocational School 2Â Semarang as evidenced by the success of the management of parks, greenery, cleanliness andÂ cultural reduce, reuce, and recycle success is supported by habits, knowledge, and real actionsÂ that requires explicit school regulation and sustainable environmental managements.AdiwiyataÂ program in State Vocational School 2 Semarang needs to be preserved, transmitted, andÂ distributed to schools or other community.Keywords : Adiwiyata, Environment, Attitude, Schoolâs Memberships